Analysis of Effect Overloading on the Remaining Life Pavement Plan on the Bungah Highway - Ngawen Highway Section - Amrullah, Muhammad Khoirun; Solichin, Ibnu; Fatikasari, Aulia Dewi (CIVED, 2024)
Bungah -Ngawen highway section is one of the accesses to the industrial area in Gresik City. This affects the vehicles that cross this road, which are dominated by heavy vehicles that distribute goods and services. These conditions can cause faster damage to the pavement which can hinder smooth transportation. This research aims to analyze the impact of vehicle loads on the remaining life of the plan on the Jalan Raya Bungah-Jalan Raya Ngawen section (STA 0+000-STA 5+500). The reason for this research is the amount of damage to the pavement. Based on a direct survey, this road has a road width of 6 m with a length of road damage of 2,15 km from the road section under review. The data used are primary data in the form of average daily traffic and secondary data, namely LHR data and vehicle load data. The calculation method used is the AASHTO 1993 Method. From the primary and secondary data obtained, traffic growth, percentage of overload, ESAL value, W18 value, and the remaining value of the road plan life can be calculated. From the calculation results, the standard ∑W18 value during the plan life is 338422516.86 to 4796885453.64, while for the overload ∑W18 value is 531674277.94 to 6849455940.63. The main trigger for pavement damage on the Jalan Raya Bungah-Jalan Raya Ngawen section is class VIb vehicles because they have the largest overload of 27,90%. The remaining life value of standard load conditions in 2024 of 57,46% decreased under overloading conditions to 33,29%, with a difference of -24,17% and the road service life will end in March 2026 or a reduction from the planned life of 10 years.